Do-not-resuscitate orders as part of advance care planning in patients with COPD. Issue 1 (16th February 2018) - Raskin, Jo; Vermeersch, Kristina; Everaerts, Stephanie; Van Bleyenbergh, Pascal; Janssens, Wim
There is growing awareness of the need for advance care planning in patients with chronic obstructive pulmonary disease (COPD). However, do-not-resuscitate (DNR) order implementation remains a challenge in clinical practice. We retrospectively analysed an observational cohort of 569 COPD patients with 2.5–8 years of follow-up in secondary care, to evaluate potential determinants and the prognostic significance of DNR order implementation and specification. 345 patients (61%) had no DNR order, of whom 27% died during a median (interquartile range (IQR)) follow-up of 1935 (1290–2448) days. 194 (39%) patients had a DNR order, of whom 17 had the order at baseline and 82% died (median (IQR) follow-up 528 (137–901) days), while 177 received an order during follow-up and 76% died (median (IQR) follow-up 1322 (721–2018) days). 88% of DNR orders were implemented during hospitalisation. 58% of the patients with a DNR order died within the first year after admission; of them, 66% died in the hospital. Age, forced expiratory volume in 1 s, chronic oxygen dependency and previous mechanical ventilation were significantly and independently associated with DNR order implementation. DNR order specification was significantly associated with increased mortality, even after adjustment for age and disease severity. These findings identify DNR orders as independent determinants of mortality, mainly implemented just before death. DNR orders in COPD patients are preferentially given to older patients with severe disease and are usually implemented during hospitalisation, close to the moment of death. Early end-of-life care planning in COPD remains difficult and challenging http://ow.ly/BGJk30hJCZ5